WAKAF SEBAGAI BENDA PUBLIK DAN PERLINDUNGAN HUKUM KEABADIANNYA TERHADAP PERALIHAN DAN PERUBAHAN FUNGSINYA - Helza Nova Lita (Universitas Islam Negeri Sumatera Utara, 2020)
Various cases of the loss of the status of waqf objects, including the change in their function, are a number of problems that occur in the practice of waqf. For example, in the re-functioning of Hagia Sophia as a mosque which was announced by the Government of Turkey, it became news that attracted international attention, including in Indonesia, where previously the building was used as a meseum. The transition of waqf objects is interesting to study considering that the change in the function of waqf has also occurred in Indonesia. For this reason, this article will discuss how the legal protection of waqf as public good against the transfer of their status and function as waqf. The method used in this article is a legal research method with a normative juridical. Waqf is a public object whose existence and function must be protected so that it is not illegally abused. The importance of protection of waqf in a comprehensive manner includes the registration and publication. Likewise, in terms of the supervision of waqf, either from the state or the government or Nazhir, which has a direct duty to supervise and manage waqf , including the active role of the community.